2014 IEEE Symposium on Security and Privacy 2014
DOI: 10.1109/sp.2014.9
|View full text |Cite
|
Sign up to set email alerts
|

Stealing Webpages Rendered on Your Browser by Exploiting GPU Vulnerabilities

Abstract: Abstract-Graphics processing units (GPUs) are important components of modern computing devices for not only graphics rendering, but also efficient parallel computations. However, their security problems are ignored despite their importance and popularity. In this paper, we first perform an in-depth security analysis on GPUs to detect security vulnerabilities. We observe that contemporary, widely-used GPUs, both NVIDIA's and AMD's, do not initialize newly allocated GPU memory pages which may contain sensitive u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…Veil does not try to stop information leaks from GPU RAM [31], but GPU RAM is never swapped to persistent storage. Poorly-written or malicious browser extensions that leak sensitive page data [32] are also outside the scope of this paper.…”
Section: Threat Modelmentioning
confidence: 99%
“…Veil does not try to stop information leaks from GPU RAM [31], but GPU RAM is never swapped to persistent storage. Poorly-written or malicious browser extensions that leak sensitive page data [32] are also outside the scope of this paper.…”
Section: Threat Modelmentioning
confidence: 99%
“…For example, Lee et al [20] found that: although they could not decode or recover original images from GPU memories, they were able to infer the sites visited by victims, by linking a targeted memory trunk with the most similar one in a labeled training set. Nevertheless, this attack is limited by some restrictions.…”
Section: Vulnerabilities In Gpusmentioning
confidence: 99%
“…Second GPU memories also hold considerable amounts of nonimage data, because modern GPUs are frequently used for nongraphical computations such as encryption and matrix calculation, which makes the problem even more complex and difficult. To address these challenges, we leverage several distinctive features of image data and have improved the prime-probe method proposed in the previous study [20]. More details are elaborated below.…”
Section: Tile Extractionmentioning
confidence: 99%
See 2 more Smart Citations